2020
DOI: 10.3390/polym12061273
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of New Amphiphilic Asphaltene Ionic Liquid Polymers to Demulsify Arabic Heavy Petroleum Crude Oil Emulsions

Abstract: Asphaltenes are heavy petroleum crude oil components which limit the production of petroleum crude oil due to their aggregation and their stabilization for all petroleum crude oil water emulsions. The present study aimed to modify the chemical structures of isolated asphaltenes by converting them into amphiphilic polymers containing ionic liquid moieties (PILs) to demulsify the emulsion and replace the asphaltene layers surrounding the oil or water droplets in petroleum crude oil emulsions. The literature surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It shows that compared to the interaction between the IAA and water molecules, the interaction between the JXGZ and water molecules is stronger. These results indicate that JXGZ possesses a better demulsification effect than reported demulsifiers [17,31,41,42] in demulsifying the asphaltene-stabilized heavy oil-water emulsions. In addition, the oxygen-containing demulsifier (MJTJU-2) we previously reported can realize the demulsification of IAA emulsions in 25 min at 60 • C [31].…”
Section: Analysis Of Demulsification Mechanism Of Jxgzmentioning
confidence: 67%
See 1 more Smart Citation
“…It shows that compared to the interaction between the IAA and water molecules, the interaction between the JXGZ and water molecules is stronger. These results indicate that JXGZ possesses a better demulsification effect than reported demulsifiers [17,31,41,42] in demulsifying the asphaltene-stabilized heavy oil-water emulsions. In addition, the oxygen-containing demulsifier (MJTJU-2) we previously reported can realize the demulsification of IAA emulsions in 25 min at 60 • C [31].…”
Section: Analysis Of Demulsification Mechanism Of Jxgzmentioning
confidence: 67%
“…ported demulsifiers [17,31,41,42] in demulsifying the asphaltene-stabilized heavy oil-water emulsions. In addition, the oxygen-containing demulsifier (MJTJU-2) we previously reported can realize the demulsification of IAA emulsions in 25 min at 60 °C [31].…”
Section: Demulsification Performance Of Jxgzmentioning
confidence: 99%
“…96 The same research group also developed amphiphilic polyionic liquids (PILs) via a different synthetic modification route to demulsify the emulsion. 97 In a recent article, Firouzi-Haji et al 98 showed the preparation of GQD-like carbon nanomaterials using asphaltenes derived from bitumen in n-heptane and oxidized and reduced versions of asphaltenes. Hence, carbon nanomaterials with various surfaces were derived.…”
Section: Chemical Modification or Synthetic Transformations Of Asphal...mentioning
confidence: 99%
“…ILs may contain different functional groups in the anion, the cation core, or both. By modification and fine-tuning of anion and cation structures, ILs with desired properties can be obtained. , Furthermore, ILs are environmentally friendly with low critical micelle concentration, non-toxic, recyclable, and non-corrosive, which are an advantage to be a green chemical candidate to prevent/minimize asphaltene instability in the presence of injected water …”
Section: Introductionmentioning
confidence: 99%